Analysis of the influence of β-TCP particle size on deagglomeration processes (Research, Society and Development, 2020)
There are a class of material widely used in bone tissue repair. This material is calcium phosphate ceramics (CPCs)that can be used on two phases: α and β. However, β-TCP is more used in bone regeneration than α–TCP due to the biocompatible and bioactive properties.In the present work evaluate the influence of these two distinct processes to deagglomeration and the consequence in the particle size of the β-TCP obtained through solid-state reaction. Among all of the routes used in research and industry to reduce the particles size of different materials, the high energy ball milling is one of the most effective, due to the high rotation speed that this process achieves. The deagglomeration through agate mortar is considered a cheaper process when compared with the high energy ball milling. The characterization of both powders, deagglomerated in high energy ball milling and agate mortar, was realized through scanning electron microscopy, to analyze the powder morphology, and laser granulometry, to determine the size of the particles. Also, the forerunner powder was previously submitted to x-ray diffraction to confirm the formation of the β-TCP phase. The analysis through x-ray diffraction confirmed that the phase formed during the calcination process corresponded to the β-TCP. The results obtained after the deagglomeration processes indicated that the morphology was predominantly irregular for both powders. In relation to the granulometry, the deagglomeration performed through agate mortar showed to produce particles with smaller size (11,4µm e 0,9µm) and heterogeneous distribution, while the high energy ball milling process produced particles with larger size (11,4µm a 1,8µm) and higher homogeneity.